2019
DOI: 10.1002/ajmg.a.61298
|View full text |Cite
|
Sign up to set email alerts
|

Equipoise of recent estimated Down syndrome live births in Japan

Abstract: To support people with Down syndrome (DS), it is essential to know and predict the number of live births of children with this condition. In this study, we estimated DS live birth rates on the basis of maternal age distribution and numbers of births in the general population, the maternal-age specific chance for a live birth of a child with DS, and the prenatal diagnosis/termination rate. The total number of live births in Japan decreased to less than 1 million in 2016 and the percentage of women aged 35 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
11
1
Order By: Relevance
“…Congenital infection is a common cause of neonatal morbidity and mortality. For example, the estimated incidence of the congenital cytomegalovirus (CMV) infection in Japan was reported to be 30 per 10,000 births between 2008 and 2010 [1], which is more frequent in comparison to trisomy 21 during the same period (i.e., 22 per 10,000 births) [2]. Meanwhile, in a nationwide survey investigating the incidence of congenital infections, Yamada et al clarified the reported incidence of congenital infections among 34 cases with CMV and 1 with Toxoplasma gondii (T. gondii) from 2714 obstetric facilities in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital infection is a common cause of neonatal morbidity and mortality. For example, the estimated incidence of the congenital cytomegalovirus (CMV) infection in Japan was reported to be 30 per 10,000 births between 2008 and 2010 [1], which is more frequent in comparison to trisomy 21 during the same period (i.e., 22 per 10,000 births) [2]. Meanwhile, in a nationwide survey investigating the incidence of congenital infections, Yamada et al clarified the reported incidence of congenital infections among 34 cases with CMV and 1 with Toxoplasma gondii (T. gondii) from 2714 obstetric facilities in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Down syndrome is the most common chromosomal abnormality in Japan 1 and occurs in 28.3/10 000 of all pregnancies. 2 It is associated with a variety of congenital malformations including heart defects (observed in 40-60% of the population), [3][4][5] duodenal atresia, anorectal malformations, hypospadias, and cataracts. 6 Down syndrome is also known to increase the risks of developing many diseases later in life, such as respiratory infections, obstructive sleep apnea, dementia, and leukemia.…”
mentioning
confidence: 99%
“…The projected number of live births with Down syndrome remained around 2200 per year between 2010 and 2016 in Japan 1 ; therefore, about 30% of them could be analysed in this study. Half of the children with Down syndrome were known to have CHD with or without abnormal haemodynamics, 8 and similarly 59.5% had it in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Down syndrome is the most common chromosomal abnormality among live‐born infants and has an estimated annual prevalence of 22 per 10,000 births in Japan 1 . The prevalence of Down syndrome live births in Japan shows a slight increase which is higher than other countries 1 . Children with Down syndrome have anatomical and physiological abnormalities which contribute to an increased susceptibility to respiratory infections.…”
Section: Introductionmentioning
confidence: 99%